(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
We are in the conviction that the loss of Present worldis education and educator due to the deficiency in the education methods or themethods that are not responding to the needs of the age. The current era isfull of controversies; one of the biggest is related with education. Allthese current problems are reasoning from incorrectly interpreting the needs of century. However, the solution way is hiddenin the problem itself i.e. good education. Whenever the minds of young brainsare not lit adequately, opinions and beliefs have met with constant disputethat followed hatred among generations and nations. Such vicious circles havereasoned from ignorance and not been educated well. The main source of solutionfor the future of globe lies in founding and opening schools at every corner ofthe world which are devoted to universal values and respectful to all humankindand opinions. With the help of these institutions and devoted educators,mobilization should be declared against ignorance, intolerance anddisrespectfulness towards universal values and besides preconceived ideasshould be subject to critics so as to give and acquire an innovative viewpointin such concepts and sciences.